2020
DOI: 10.9758/cpn.2020.18.2.219
|View full text |Cite
|
Sign up to set email alerts
|

The Neurochemical Effects of Prazosin Treatment on Fear Circuitry in a Rat Traumatic Stress Model

Abstract: Objective: The timing of administration of pharmacologic agents is crucial in traumatic stress since they can either potentiate the original fear memory or may cause fear extinction depending on the phase of fear conditioning. Brain noradrenergic system has a role in fear conditioning. Data regarding the role of prazosin in traumatic stress are controversial. Methods: In this study, we examined the effects of prazosin and the noradrenergic system in fear conditioning in a predator stress rat model. We evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…Neuronal cell damage to the mPFC, Hipp, and Amg (i.e., the fear circuit region of the brain) caused by PTSD impairs the acquisition of fear-extinction learning [ 31 ]. Our results showed that in the CFT, SPS-exposed rats had significantly increased freezing behavior after traumatic contextual fear and fear response during the extinction recall.…”
Section: Discussionmentioning
confidence: 99%
“…Neuronal cell damage to the mPFC, Hipp, and Amg (i.e., the fear circuit region of the brain) caused by PTSD impairs the acquisition of fear-extinction learning [ 31 ]. Our results showed that in the CFT, SPS-exposed rats had significantly increased freezing behavior after traumatic contextual fear and fear response during the extinction recall.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in glutamatergic and GABAergic transmissions have been reported in schizophrenia, depression, PTSD, and obsessive-compulsive disorder [ 237 , 238 , 239 , 240 , 241 , 242 , 243 ]. Moreover, studies on the role of these neurotransmitter systems in mental disorders seem to be promising for better understanding etiopathogenetic mechanisms, as well as for improving the effectiveness of pharmacological therapies [ 244 , 245 , 246 , 247 , 248 , 249 , 250 ]. Although direct evidence on the role of glutamatergic and GABAergic transmissions in active memory forgetting in psychopathological disorders is still lacking, it is possible to hypothesize that dysfunctions of these neurotransmitter systems are a common basis for deficits in active forgetting observed in the different psychopathologies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, targeting these symptoms is critical in the beneficial treatment of resistant PTSD [22]. Most specialists approve that PTSD and obstinate nightmares should not be regarded as treatment-refractory unless it has had an adequate prazosin trial [23][24][25]. However, prazosin, an α1-blocker, isn't available in Italy, and we considered an alternative strategy.…”
Section: Discussionmentioning
confidence: 99%